Avaliação da padronização dos procedimentos nas salas públicas de vacinas do município de Itabaiana, Sergipe, Brasil (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Assessment of Standardization of the Procedures in the Public Vaccination Facilities in the Municipality of Itabaiana, Sergipe, Brazil